Teoretyczne i metodologiczne trudności w badaniach nad konfliktami zbrojnymi w naukach społecznych. Przykład Kolumbii. - Wereta, Karolina (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
The article carries out a reflection on practical, theoretical and methodological problems faced by social science researchers investigating armed conflicts. Based on Colombia’s ongoing internal war, the paper will discuss the difficulties in data collection (including source selection and information extraction), data sharing and the limitations of exiting theoretical language. It will also exploit other related factors such as the fragmentation of sociological research and the growth of publications regarding the conflict, violence, and the peace processes initiating in Colombia. In the presented article, the author analysis both governmental and non-governmental reports and also outlines several key cultural and political issues affecting data collection and their further publication in Colombia.